Rapid submarine melting driven by subglacial discharge, LeConte Glacier, Alaska. Issue 19 (10th October 2013) - Motyka, Roman J; Dryer, William P; Amundson, Jason; Truffer, Martin; Fahnestock, Mark
<x xml:space="preserve">Abstract</x> [1] We show that subglacial freshwater discharge is the principal process driving high rates of submarine melting at tidewater glaciers. This buoyant discharge draws in warm seawater, entraining it in a turbulent upwelling flow along the submarine face that melts glacier ice. To capture the effects of subglacial discharge on submarine melting, we conducted 4 days of hydrographic transects during late summer 2012 at LeConte Glacier, Alaska. A major rainstorm allowed us to document the influence of large changes in subglacial discharge. We found strong submarine melt fluxes that increased from 9.1 ± 1.0 to 16.8 ± 1.3 m d−1 (ice face equivalent frontal ablation) as a result of the rainstorm. With projected continued global warming and increased glacial runoff, our results highlight the direct impact that increases in subglacial discharge will have on tidewater outlet systems. These effects must be considered when modeling glacier response to future warming and increased runoff.